The Level of Student Learning Independence: Between the Future Goals and Facts - Sofyan Rofi; Dahani Kusumawati; Tri Endang Jatmikowati (Jurnal Pendidikan Islam Indonesia, 2022)
The level of student learning independence is a representation of the manifestation of various aspects both from internal and external factors of the students. The existence of motivation has an impact on self-awareness, creative, and critical attitudes of the students. It is also related to the effectiveness and efficiency of learning experienced by students. The role and the influence of learning independence can encourage student success in competency development. This study aims to look at the level of student learning independence in three SMP Muhammadiyah (Muhammadiyah Junior High School) in Jember, both as a whole and based on the gender of the students. This study uses a qualitative approach which research instrument is in the form of a questionnaire. The form of the answer is a choice using Likert scale which score range is 5-1 meaning positive-negative scale. The research respondents were 491 students of three schools. The data analysis techniques use percentages linked to five tabulation categories. The research results of those three schools illustrate that the level of student learning independence are good. Meanwhile, based on the gender aspect, the female students level of learning independence is higher than male students. Besides, the indicators having the lowest percentage on the aspect of student independence are making question examples and summaries of learning material.